"Go out and study the land" (Judges 18:2) : archaeological, historical and textual studies in honor of Hanan Eshel - Eshel, Ḥanan.; Maeir, Aren M.; Magness, Jodi.; Schiffman, Lawrence H. (Supplements to the Journal for the Study of Judaism, 2012)
Hanan Eshel (z\'l) was a prolific scholar in the field of Dead Sea Scrolls, Classical Archaeology of the Near East and many other topics. During his terminal illness, friends and colleagues got together to present him with a collection of studies on topics that were close to his fields of interest, as an expression of deep friendship and admiration. The volume contains the 22 papers presented to Hanan before his death, covering topics in archaeology, history, and textual studies, with a particular emphasis on aspects relating to the Dead Sea Scrolls, spanning the late Iron Age through late Antiquity.